(untitled) (The Macau Ricci Institute Journal, 2023)
The world is witnessing yet another global geopolitical shift, the most significant since the successful implementation of the Marshall Plan or the European Recovery Program, for the postwar reconstruction of Europe (1948-1951). This third millennium witnesses the Belt and Road Initiative (BRI) that is integral to the ’China Dream’. The explanation of the vision and goals of BRI is presented in section one in relation to China’ collaboration with ASEAN and Africa, with Ethopia and Pakistan as two case studies. These allow an appraisal of how China intends her foreign aid program to improve the quality of life of countries of the global South with its integrated assistance programs. As a basis for the appraisal outlined in section 1, we propose the model of a new integral ecology, derived from Pope Francis’ Laudato Si’ (LS) Fratelli Tutti (FT). These provide a constructive critique of the foundational presuppositions of the foreign aid policies of the BRI.